Reconciliação urbana : análise simbólica da paisagem da Vila da Vitória (séc. XVI-XVIII) - Lima, Bruno de Oliveira (2013)
This dissertation focuses the landscape of the Village of Vitoria (century XVI – XVIII). The spatial structure of this village was filled with strong symbolic connotation and that "construction of meaning" was expressed in their territorial conformation a